Cross-National Perspective on Early Childhood Education Engaging in Inquiry - Takanishi, Ruby. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1976)
Some potential areas of inquiry into the field of cross-national study of early childhood education are described in relation to the history and aims of the World Organization for Early Childhood Education (OMEP). Currently the largest international organization concerned with preschool education, OMEP is presented with specific recommendations: (1) that members, possibly by regions, select and focus on one country or region, (2) that OMEP establish organizational linkages with other groups working in the area of cross-national studies, and (3) that OMEP foster the goal of cross-national studies as understanding and development of the field, rather than for purposes of comparison and criticism. Need is seen for developing systematic descriptive frameworks for organizing inquiry and for observing programs. Some neglected areas are: cross-national study of policy formation; observation of teacher-child, child-child and child-material interaction in programs; and the study of regional and ethnic cultural variations and educational beliefs and practices where there is no homogeneous national pattern. It is stressed that observations of teacher practices and children's behavior be interpreted within the goals and concepts of the particular culture and society. (Author/BF)
ERIC Note: Paper presented at the Annual Meeting of the U.S. National Committee, World Organization for Early Childhood Education (Anaheim, California, November 10, 1976).
Educational level discussed: Early Childhood Education.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Comparative Education; Cross Cultural Studies; Cultural Differences; Early Childhood Education; Foreign Countries; Individual Development; International Education; International Organizations; Political Influences; Research Needs; Socialization; World Organization for Early Childhood Education; Speeches/Meeting Papers